Studies on antioxidant and cytotoxic activities of dichloromethane extract of Marasmius species / Teesilia Mohamed Nor - Mohamed Nor, Teesilia (2012)
Although much research has been focused on the therapeutic and medicinal effects of wild mushrooms, there is still paucity of information on the pharmacological properties of Marasmius species. The present study was undertaken to evaluate the cytotoxic and antioxidant activities of M. guyanensis (KUM 20044, KUM 20222, and KUM 20117), M. kanchingnensis (KUM 20160), Marasmius sp. (KUM 20067), M. ruforotula (KUM 20111, KUM 20112) and M. selangorensis (KUM 20181). Crude dichloromethane extracts were prepared from the mycelial biomass grown in liquid Glucose-Yeast-Malt- Peptone (GYMP) using a soxhlet extractor system. The cytotoxic effect of the Marasmius extracts was screened using Neutral Red assay (NR). At 20 μg/ml, all the extracts demonstrated less than 50% inhibition against the cancer cell lines tested, namely human mouth epidermal carcinoma cell line (KB), human epidermal carcinoma of cervix cell line (CaSki), human colon cancer cell line (HT 29), human intestinal colon cancer cell line (HCT 119), human colorectal cancer cell line (SKOV 3), human breast cancer cell line (MCF 7) and also on normal human fibroblast cell (MRC 5). These extracts were therefore regarded as not actively cytotoxic against the cancer cell lines. At 20 μg/ml, crude dichloromethane extract of M. guyanensis (KUM 20044) showed the highest percentage inhibition activity of 37.7% ± 1.82 against SKOV 3 cells followed by M. ruforotula (KUM 20111) (34.6% ± 2.22) and M. guyanensis (KUM 20222) (33.8% ± 3.35). Crude extracts of M. guyanensis (KUM 20222) exhibited the highest percentage inhibition against MCF 7 and HT 29 cancer cells with inhibition of 23.2% ± 1.30 and 40.7% ± 3.76 respectively at 20 μg/ml. For HCT 119 cells, crude extracts of M. ruforotula (KUM 20111, KUM 20112) and M. selangorensis (KUM 20181) gave the highest percentage of inhibition of 37.0% ± 3.72, 35.5% ± 3.58 and 33.4% ± 3.67, respectively. Similarly, M. ruforotula (KUM 20111) exhibited the highest percentage of inhibition of 47.2% ± 2.04 towards KB cells followed by M. ruforotula (KUM 20112) with a value of 46.9% ± 0.84 and 46.9% ± 2.20 for M. selangorensis (KUM 20181). Among the extracts, Marasmius sp. (KUM 20067) showed the highest percentage of inhibition of 32.0% ± 2.59 against CaSki cells. The antioxidant potency was investigated by employing three established in vitro systems such as 2,2-diphenyl,1-picrylhydrazyl (DPPH) radical scavenging, reducing power and metal chelating assays. The extracts exhibited slow kinetic reaction with the DPPH radicals with extracts taking about 60 minutes to reach a steady state scavenging abilities. Based on the EC50 values, the effectiveness as DPPH radical scavengers were arranged in descending order: M. kanchingnensis (KUM 20160) 67.49 ± 0.004> M. guyanensis (KUM 20222) 77.56 ± 0.004 > M. ruforotula (KUM 20111) 79.90 ± 0.004 > M. ruforotula (KUM 20112) 91.70 ± 0.004 > M. selangorensis (KUM 20181) 99.50 ± 0.022> M. guyanensis (KUM 20117) 102.65 ± 0.037 > M. guyanensis (KUM 20044) 141.80 ± 0.007> Marasmius sp. (KUM 20067) 150.78 ± 0.015. Based on the reducing power assay, M. selangorensis (KUM 20181) exerted good reducing power abilities of 1.772 nm at 20 mg/ml. In the metal chelating assay, the absorbance reading of all the crude extracts are relatively low which indicates they are exhibiting weak chelating effects on ferrous ion at all concentration tested.